Pengaruh Pendekatan Pakem Terhadap Keterampilan Mengukur Dan Mengklasifikasikan Ukuran Benda Dalam Pembelajaran Sains Anak Kelompok B - Yusnira Yusnira (LPPM Universitas Pahlawan Tuanku Tambusai, 2015)
PAKEM approach can be applied in teaching science. Preliminary observations on Pembina Bangkinang kindergarten children learning science is rarely done, especially activities to measure and classify the size of the objects have never been implemented. This gap into the background of this research. Research the type of pre-experimental design with one group pre-test post-test design. collecting data through observation with the observation assessment tool sheet. The subjects of the study all children amounted to 22 children. Data were analyzed using non-parametric statistical test level Wilcoxon signed by the formula tcount t table, where if thitung smaller than ttabel the significant results of this study the influence of two variables. Based on the result ttabel ( = 0.05) = 66 and t = 0 so thitung- ttabel (0 66). It can be stated no significant effect on the measuring and classifying skills, where the maximum score on the skills of the measure is 19 and 7 on classifying skills and after the treatment is given the maximum score on the skills of the measure is 24 and 8 on classifying skills